Disseminação de íons cloreto na orla marítima do bairro de Boa Viagem, Recife-PE - Pontes, Ronaldo Bezerra (2006)
Exposing concrete structures to the saline mist, they can suffer chlorides attacks and could cause reinforcement corrosion. The structures parts with faces directed to dominant winds are more susceptible, especially those with great surface in relation to the volume, such as pillars and beams. This work objective is to evaluate the level of marine aggressiveness, in marine edge of Boa Viagem quarter, Recife-PE, in function of the distance to the sea, measuring the value of chloride deposition, using the wet candle method, with the support of the environment management. The results indicate that chloride ions reach surface structure in different levels of concentration, depending on the distance from its origin, in this case, the sea. The conclusion is that chloride deposition decreases, in an exponential relation, when there is an increase of the distance to the sea, and that aggressiveness is significantly as far as 400 m from the marine edge